Purely Neuroendoscopic Resection of an Intraventricular Cavernous Angioma: Case Report - Giannetti, Alexandre Varella (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background Intraventricular cavernomas are rare and generally treated by microsurgical approach. With the advances in neuroendoscopy, intraventricular lesions have been managed by this technique. However, tumor size and vascular nature are considered restrictive factors. As far as we are concerned, there are two cases in the literature of intraventricular cavernoma resection done by neuroendoscopy.Case We describe a case of a man who presented with hydrocephalus secondary to a mesencephalic cavernoma and a second cavernous angioma located at the dorsum thalamus. This second lesion was successfully removed using a pure neuroendoscopic technique at the same time as a third ventriculostomy was performed.Conclusion As neuroendoscopy evolves, we see that lesions considered impossible to be managed by neuroendoscopy before today are being treated with the advantages that the minimally invasive surgery offers.
Keywords: cavernoma; vascular NS; endoscopy; cerebral ventricle; minimal invasive; hydrocephalus